Analisis Pembelajaran Berdiferensiasi Perkembangan Intelektual Pserta Didik Sekolah Dasar - Hutabarat, Keren Hapug; Luhukay, Michelya Zabrina; Putri, Zaskia Rachmadini; Mustikaati, Wina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Differentiated learning is an instructional approach aimed at tailoring the teaching and learning process to match the readiness, interests, and learning profiles of each student. This article seeks to analyze the role of differentiated learning in the intellectual development of students. Through a qualitative approach based on literature review, it was found that differentiated learning not only enhances student engagement and motivation but also significantly contributes to their cognitive abilities. Implementing differentiation strategies in content, process, product, and learning environment creates an adaptive and inclusive learning space. However, the approach also faces challenges such as time constraints, teacher readiness, and perceptions of unfairness among students. Therefore, support in the form of teacher training, effective classroom management, and flexible curricula is essential. In this way, differentiated learning becomes a strategic solution for creating meaningful and balanced learning experiences for all students.